SISTEM PENDETEKSI PENULISAN KATA PADA DOKUMEN BERBASIS WEB - andika Saputra; Dwi Sakethi; Yohana Tri Utami (Jurnal Komputasi, 2021)
The process of detecting writing errors manually takes a lot of time and requires a source of reference to prove the truth of writing words. The efficiency of time required if done manually certainly will not be optimal, so we need a word writing error detection utility that is expected to make it easier to check errors in a document of type word (.docx). In the process of developing this utility through several stages of the process, namely Cleansing, Case Folding, Tokenization, Stemming and Dictionary Lookuup. The result of the docx document being processed is influenced by the completeness of the dictionary used as a reference for word correction and the type of word spelling errors